METHOD FOR RECYCLING PHOSPHOR - NISHIDA SATOSHI; KAWAI TAKAO (2003)
PROBLEM TO BE SOLVED: To provide a method for recycling a so-called degraded phosphor having reduced luminance that is recovered from used fluorescent lamps and cathode ray tubes, in which chemical treatment is unnecessary; the advantages that a waste phosphor can be economically and efficiently recycled are made to be best use of; and even when the time for reduction is increased when a phosphate phosphor is used as a blue phosphor, a red phosphor is not degraded. SOLUTION: The degraded phosphor is subjected to reduction treatment in a reducing atmosphere of 1,500°C or below, while steam is added to the reducing atmosphere. COPYRIGHT: (C)2003,JPO